KARAKTERISTIK FISIKA DAN pH SEDIAAN LIPOSOM KOENZIM Q10DAN GLUTATHION SEBAGAI ANTI AGING - Sofani Lega Armia; Ni Luh Dewi A. (Perpustakaan Universitas Surabaya, 2018)
Abstract - Skin aging is a biological process that occurs naturally and coincides with increase of the age. But extrinsic factor caused free radical is a major factor that accelerates skin aging. Coenzym Q10 and Glutathione have high antioxidant activity that can prevent skin cell damage caused by free radical. In this research is made cosmetic antiaging formulations with liposomal delivery system to increase skin penetration. Formulation liposomes made with 2 formula used thin film hydration method. First formula is a basis of liposome, and second formula is a liposome with Coenzym Q10 and Glutathione. A liposome and liposome base formulation has been performed with the active ingredient Coenzyme Q10 and Glutathione to physical and pH characteristics. The result of this study are two formulations show that there is difference in the physical character consisting of organoleptic, particle size, and specifications for entrapment of drug not meeting specifications. However, there is no difference in pH.